Features of the Formation of Musical Taste in the Preparatory Group in a Preschool Institution (Journal of Pedagogical Inventions and Practices, 2022)
The article deals with topical issues of educating the artistic taste of a preparatory group for school by means of musical art. The processes of its formation are considered, including the goal, objectives, content of music education, psychological and pedagogical conditions, means, organizational forms and methods; features of the process under study in the music lesson, reveals the pedagogical potential of the complex application of various types of musical activities of children.